Implementasi Kebijakan Penataan Ruang Publik Melalui Penertiban Tiang Reklame di Kota Pekanbaru - Malika Alya Kasta; Hafzana Bedasari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The public space planning issues in Pekanbaru are not merely technical in nature, but reflect weak policies in controlling land use, which is influenced by economic interests. This study aims to analyze the implementation of policies regulating billboard poles and the factors causing their ineffectiveness using a qualitative approach through interviews, observations, and documentation, and analyzed using Merilee S. Grindle’s policy implementation perspective. The results of the study indicate that although regulations are in place, their implementation has not been effective; enforcement on the ground tends to be administrative and ad hoc, and has not yet become part of a structured control system. The policies have also failed to curb the growth of illegal billboards because they do not address the root of the problem namely, the strong economic interests of business operators that undermine the enforceability of the rules resulting in compliance that is temporary and situational. In additional, weak oversight, limited resources, and a lack of coordination among agencies indicate institutional capacity deficiencies. These conditions have led to policies becoming trapped in a cycle of repeated enforcement without yielding significant changes in public space planning; therefore, institutional capacity building, consistent regulatory enforcement, and the management of economic interests are necessary to ensure that policies can be implemented more effectively and sustainably.